Simplicillium sinense sp. nov., a novel potential pathogen of tinea faciei - Yan, Qiu-Hong; Ni, Qing-Rong; Gu, Wei-Jie; Liu, Hong-Wei; Yuan, Xiao-Ying; Sun, Jing-Zu (Frontiers in Microbiology, 2023)
Simplicillium species are widely distributed with a broad spectrum of hosts and substrates. Generally, these species are entomopathogenic or mycoparasitic. Notably, some isolates of Simplicillium lanosoniveum and Simplicillium obclavatum were obtained from human tissues. In this study, two fungi were isolated from the annular itchy patch of infected skin of a 46-year-old male with diabetes mellitus. Based on a combination of morphological characteristics and phylogenetic analysis, a novel species, Simplicillium sinense was introduced herein. It morphologically differs from the remaining Simplicillium in the size of phialides and conidia. Additionally, it grows slowly on YPD at 37 ℃. Antimicrobial susceptibility testing presented that this fungus is resistant to most azole antifungals. Therefore, the diagnosis of tinea faciei was made and after two weeks of being treated with oral terbinafine (250mg, once a day) and topical terbinafine cream for 1 month, the rash was mainly resolved and no recurrence happened after six months of follow-up. Herein, Simplicillium sinense was introduced as a new fungal taxon. Meanwhile, a case of superficial infection caused by S. sinense was reported. So far, it is the third Simplicillium species obtained from human tissue. Meanwhile, terbinafine is recommended as the first-line antifungal treatment against Simplicillium infection.